Business Despite Borders Companies in the Age of Populist Anti-Globalization (Springer International Publishing, 2018)
Globalization has been a key force in the development of business in recent decades. But with nationalism on the rise in Europe, the United States and elsewhere, the future of global trade and international business has been thrown into doubt. In this new and challenging context, innovative companies have the opportunity not only to find new ways to operate across borders, but also to help forge a new system of relations between people of different nationalities and cultures. This book features a collection of case studies that illustrate how companies from different corners of the globe are succeeding in reaching out to distant customers, stakeholders and partners. It features inspiring examples of leaders who are actively developing imaginative ways to connect across continents. It is a vital reference tool for companies that plan to continue operating globally or to expand their international presence. A clarion call for the renewed relevance and importance of globalized business, this book suggests a future where companies can contribute positively to achieving sustainable growth and a fairer distribution of wealth across the globe.